Method for bonding surface nanocrystallization copper columns in air environment

By electrochemically preparing nanocrystalline copper layers and performing Cu-Cu bonding in low-temperature and low-pressure air environments, the reliability and environmental dependence of traditional solder joints are solved, and high-quality low-temperature interconnection is achieved, suitable for high-density chips Package.

CN119275178AActive Publication Date: 2025-01-07DALIAN UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411389306.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Traditional Sn-based solder joints have reliability problems such as solder extrusion, bridging and brittle Cu-Sn intermetallic compound fracture during miniaturization, which is difficult to meet the packaging requirements of high I/O density chips, and the high temperature of Cu-Cu joints , high pressure, high flatness and high vacuum environments limit their wide application.

Method used

The nanocrystalline copper layer was prepared by electrochemical methods, and the copper oxidation was prevented by organic films. The Cu-Cu direct bonding was achieved in a low-temperature and low-pressure air environment combined with the hot pressing process, reducing the bonding temperature and flatness requirements, and using resistance High-temperature photoresist acts as a thermal conductivity medium to avoid chemical mechanical polishing.

Benefits of technology

Achieve high-quality Cu-Cu interconnects in low-temperature air environments, improve joint strength and electrical performance, simplify processes, reduce costs, and is suitable for three-dimensional and ultra-fine pitch packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275178A_ABST
    Figure CN119275178A_ABST
Patent Text Reader

Abstract

The invention discloses a method for bonding surface nanocrystallization copper columns in an air environment, and belongs to the field of electronic packaging. The method comprises the following steps: depositing metal Ti and Cu on a silicon substrate; photoetching and developing to prepare an array pattern; a copper column array is obtained through electro-deposition; preparing a Cu nanowire array through anodic oxidation electrochemical reduction; and preparing an organic reducing agent, coating and carrying out thermocompression bonding. The patterned copper nanowire array salient points can be prepared, and the high-temperature-resistant photoresist is combined to serve as a heat-conducting medium, so that an additional filling step is not needed; high-quality copper-copper interconnection can be realized in a low-temperature air environment, and the defects of overhigh copper interconnection temperature and dependence on a bonding environment are overcome; the copper nanowires with a certain height are compressed in the direction perpendicular to the substrate during interconnection, the requirement for surface flatness is lowered, the chemical mechanical polishing process is not needed, and meanwhile the interconnection defect caused by alignment deviation is overcome. The method is simple in preparation process, low in cost and suitable for a low-temperature interconnection technology for three-dimensional packaging and superfine pitch packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic packaging, and in particular relates to a method for bonding surface nano-copper columns in an air environment. Background Art

[0002] With the development of the miniaturization trend of electronic products, the size of chips and other electronic components is getting smaller and smaller, and the requirements for electronic packaging interconnection joints are getting higher and higher. Traditional Sn-based solder joints will have major reliability problems such as solder extrusion, bridging, and brittle Cu-Sn intermetallic compound fracture when the interconnection pitch is miniaturized. It is difficult to meet the packaging requirements of extremely high I / O density chips in emerging industries (such as artificial intelligence, autonomous driving, Internet of Things, 5G networks, etc.), and it is urgent to explore more suitable interconnection solutions.

[0003] Cu-Cu bump interconnection is considered to be an interconnection technology with higher density and reliability. Compared with Sn-based solder joints, Cu-Cu joints do not bridge adjacent pads and can support higher interconnection density; Cu has more excellent anti-electromigration, electrical and thermal conductivity, good processability and low cost. Although Cu-Cu joints have great advantages, their interconnection requires high temperature, high pressure, high surface flatness, and high vacuum or reducing environment, which limits their wide application in industry.

[0004] How to reduce the temperature, pressure, atmosphere and flatness of copper-copper interconnection is very important for the promotion and application of this technology. Researchers prepare nanocrystalline copper layers to reduce the bonding temperature, use some organic substances to prevent the copper surface from being oxidized, and use nanoporous or nanowire structures to reduce the requirements for flatness. Although the harsh conditions required for copper-copper bonding technology have been reduced, there are still problems such as the complex preparation process of copper nanowires (requiring H2 and other reduction), the single function of the organic protective layer (only preventing copper oxidation), and the gaps between the substrates after bonding, resulting in poor heat dissipation. Summary of the invention

[0005] To solve the above problems, the present invention provides an interconnection method for realizing Cu-Cu direct bonding in a low-temperature, low-pressure air environment by protecting nano copper wires with an organic layer. In this method, the copper nanowires are prepared by an electrochemical method, the organic film can prevent the oxidation of the nano copper wires, and the organic layer combined with the corresponding hot pressing process will not hinder the diffusion of copper atoms at the bonding interface. The copper nanowire interconnection structure does not require chemical mechanical polishing, and the resulting joint has high strength and excellent electrical properties.

[0006] The present invention can prepare patterned copper nanowire array bumps, and combined with high temperature resistant photoresist as a heat conducting medium, no additional filling steps are required; high-quality copper-copper interconnection can be achieved in a low-temperature air environment, overcoming the high temperature of copper interconnection and dependence on the bonding environment; copper nanowires of a certain height are compressed in the direction perpendicular to the substrate during interconnection, reducing the requirements for surface flatness, no chemical mechanical polishing process is required, and the interconnection defects caused by alignment deviation are improved. The present invention has a simple preparation process and low cost, and is suitable for low-temperature interconnection technology for three-dimensional packaging and ultra-fine pitch packaging.

[0007] The technical solution adopted by the present invention is:

[0008] A method for bonding surface nano-copper pillars in an air environment comprises the following steps:

[0009] (1) first depositing a metal Ti seed layer on a silicon substrate, and then depositing a metal Cu seed layer; then applying a photoresist on the silicon substrate by a spin coating method, and baking, exposing and developing are performed in sequence to form a column;

[0010] (2) preparing a copper hydroxide (Cu(OH)2) nanowire solution: adding sodium hydroxide into deionized water and stirring until the sodium hydroxide is completely dissolved;

[0011] (3) Electrodepositing copper pillar array: electroplating copper to fill the silicon substrate after photolithography in step (1), washing with deionized water and drying with nitrogen after electroplating;

[0012] (4) Preparation of Cu(OH)2 nanowires: The silicon substrate obtained in step (3) is used as an anode, a platinum sheet is used as a cathode, and an Ag / AgCl saturated potassium chloride electrode is used as a reference electrode. The cathode, anode and reference electrode are placed in an electrolytic cell of the nanowire solution obtained in step (2), and an anodization is performed using an electrochemical workstation three-electrode system and a constant potential method. After the anodization is completed, the power supply is turned off, the silicon substrate of the anode is taken out from the nanowire solution, rinsed with deionized water and dried, and Cu(OH)2 nanowires are formed on the top of the copper column;

[0013] (5) annealing the Cu(OH)2 nanowires obtained in step (4) in air to thermally decompose the Cu(OH)2 nanowires into CuO nanowires;

[0014] (6) preparing potassium hydroxide electro-reducing solution: adding potassium hydroxide into deionized water and stirring until completely dissolved;

[0015] (7) electro-reducing the CuO nanowires to Cu nanowires: using the silicon substrate with CuO nanowires grown thereon obtained in step (5) as a cathode, graphite as an anode, and an Ag / AgCl saturated potassium chloride electrode as a reference electrode, and performing constant potential polarization in the potassium hydroxide electro-reduction solution obtained in step (6) using an electrochemical workstation until the current is stable and the cathode surface changes from black to reddish brown, the CuO nanowires are electro-reduced to Cu nanowires, and copper pillar array bumps with Cu nanowires on the surface are obtained on the silicon substrate;

[0016] (8) The silicon substrate with Cu nanowire array bumps obtained after electro-reduction is placed in an organic reducing agent, and in a low vacuum environment below 0.1 MPa, the organic matter forms a dense protective film on the Cu nanowires. Then, the silicon substrate with the Cu nanowire array bumps is taken out, the upper and lower bumps of the two silicon substrates are aligned, and the two silicon substrates are placed in a bonding machine, and hot-pressed sintering is performed at 150-300° C. and 0-20 MPa for 10-30 min.

[0017] The diameters of the Cu(OH)2 nanowires and CuO nanowires are 50-200nm.

[0018] More preferably, in step (1), the thickness of the metal Ti seed layer is 10-100 nmTi, and the thickness of the metal Cu seed layer is 100-500 nm.

[0019] More preferably, in step (2), the concentration of sodium hydroxide is 0.1 to 1 M / L.

[0020] More preferably, the working voltage applied in step (4) is -200 mV to -100 mV relative to the reference electrode.

[0021] More preferably, in step (5), the annealing temperature of the Cu(OH)2 nanowires is 180-220°C, and the annealing time is 1-3h.

[0022] More preferably, in step (7), the concentration of potassium hydroxide is 0.1-1 M / L.

[0023] More preferably, the working voltage applied in step (7) is -0.8 V to -1.2 V relative to the reference electrode.

[0024] More preferably, the organic reducing agent used in step (8) is: ethylene glycol, polyethylene glycol, polyvinyl pyrrolidone, ascorbic acid, citric acid, glycerol, 3-dimethylamino-1,2-propylene glycol (DMAPD), formic acid, acetic acid, one or a mixture of two or more thereof.

[0025] Beneficial effects of the present invention:

[0026] (1) The present invention uses a thermal oxidation decomposition combined with an electrochemical reduction method to prepare copper nanowire array bumps with a diameter ranging from 50 to 200 nm on a silicon substrate, thereby reducing the temperature, pressure and other conditions required for copper-copper direct bonding.

[0027] (2) The coating of the organic film on the surface of the copper nanowires can prevent the copper nanowires from oxidizing in the air environment. At the same time, the organic matter can reduce copper oxide when heated, making it difficult to produce CuO when the copper nanowire array is hot-pressed and bonded in the air environment, thereby avoiding the need for a vacuum or reducing environment.

[0028] (3) The copper nanowire array bumps can achieve compressive deformation in the direction perpendicular to the substrate, and no chemical mechanical polishing is required before bonding. At the same time, the interconnection defects caused by alignment deviation can be improved.

[0029] (4) The present invention has a simple preparation process, low cost, and great application value, and is suitable for low-temperature interconnection technology for three-dimensional packaging and ultra-fine pitch packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is the experimental flow chart in the embodiment.

[0031] Figure 2 The surface SEM image and EDS composition analysis results of the copper hydroxide nanowires prepared by anodization in Example 1.

[0032] Figure 3 The surface SEM image and EDS component analysis result of copper oxide nanowires obtained by heating and decomposing copper hydroxide in Example 1.

[0033] Figure 4 The surface SEM image and EDS component analysis result of the copper nanowires prepared after the copper oxide nanowires obtained in Example 1 were electro-reduced. DETAILED DESCRIPTION

[0034] The embodiments of the present invention are described in detail below with reference to the examples. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. Figure 1 Follow the steps shown.

[0035] Example 1

[0036] (1) A metal seed layer of 100 nm Ti and 100 nm Cu was magnetron sputtered on a silicon substrate, and then a photoresist was spin-coated on the substrate, baked, exposed, and developed.

[0037] (2) Electroplating and filling copper pillars: The substrate in step (1) is used as a cathode for electroplating and filling copper. After filling, it is washed with deionized water and dried with cold air for standby use.

[0038] (3) Preparation of anodized copper nanowire solution: 4 g of sodium hydroxide was added to 100 mL of deionized water, the solution was ultrasonically dispersed for 10 min, and then magnetically stirred for 10 min at a speed of 500 r / min.

[0039] (4) Using an electrochemical workstation and a three-electrode system, the copper-filled silicon wafer electroplated in step (2) is used as a working electrode, the platinum electrode is used as a counter electrode, and Ag / AgCl saturated potassium chloride is used as a reference electrode. The distance between the working electrode and the counter electrode is 3 cm. The working electrode, the counter electrode and the reference electrode are placed in an electrolytic cell filled with sodium hydroxide solution for constant potential oxidation. The oxidation potential is -200 mV relative to the reference electrode and the temperature is 25°C.

[0040] (5) After 2 h of oxidation, the electrochemical workstation was turned off, the working electrode was removed from the solution, rinsed with deionized water, and dried to obtain Cu(OH)2 nanowire array micro-bumps, such as Figure 2 As shown, the SEM morphology of the sample shows that the nanowire diameter is in the range of 100 nm.

[0041] (6) The Cu(OH)2 nanowires were placed in an annealing furnace, heated to 220°C at a rate of 10°C / min and kept at that temperature for 1 h. After air cooling, the CuO nanowire arrays were obtained. Figure 3 As shown, the SEM image shows that the CuO obtained by annealing Cu(OH)2 nanowires still maintains the nanowire morphology, and EDS composition analysis proves that the annealing product is CuO.

[0042] (7) To prepare an electrochemical reduction solution of CuO, 0.56 g of potassium hydroxide was added to 100 mL of deionized water, and the mixture was ultrasonically dispersed for 10 min, and then magnetically stirred for 10 min at a speed of 500 r / min.

[0043] (8) Using an electrochemical workstation and a three-electrode system, the sample in step (6) is used as the working electrode, the platinum electrode is used as the counter electrode, and Ag / AgCl saturated potassium chloride is used as the reference electrode. The distance between the working electrode and the counter electrode is 3 cm. The working electrode, the counter electrode, and the reference electrode are placed in an electrolytic cell filled with potassium hydroxide solution and subjected to constant potential polarization. The polarization potential is -0.8 V relative to the reference electrode and the temperature is 25°C. When the current no longer changes and the surface of the working electrode changes from black to reddish brown, as shown in FIG. Figure 4 As shown, the SEM image shows that the Cu obtained after electro-reduction still maintains the nanowire morphology, and the EDS composition analysis shows that the oxygen content of the electro-reduction product is greatly reduced, proving that CuO is reduced to Cu.

[0044] (9) The copper nanowire array substrate of the working electrode was taken out, and the residual solution on the surface was cleaned with ethylene glycol, and then placed in an ethylene glycol solution containing 0.5 g PVP, 0.1 g ascorbic acid, and 0.5 g glycerol. The substrate was placed in a low vacuum environment of 0.08 MPa for 20 min to allow the organic reducing substances to evenly cover the copper nanowires.

[0045] (10) The bumps of the copper nanowire array substrate coated with an organic reducing film were aligned and placed in a hot press bonding machine. In an air environment, a pressure of 2 Mpa was applied and heated to 250 °C at 10 °C / min. After keeping the temperature for 1 min, the bonded sample was taken out and air-cooled to room temperature. The shear strength of the bonded joint was tested and the strength was higher than 10 Mpa.

[0046] Example 2

[0047] (1) A metal seed layer of 10 nm Ti and 500 nm Cu was magnetron sputtered on a silicon substrate, and then a photoresist was spin-coated on the substrate, baked, exposed, and developed.

[0048] (2) Electroplating and filling copper pillars: The substrate in step (1) is used as a cathode for electroplating and filling copper. After filling, it is washed with deionized water and dried with cold air for standby use.

[0049] (3) Preparation of anodized copper nanowire solution: 0.4 g of sodium hydroxide was added to 100 mL of deionized water, the solution was ultrasonically dispersed for 10 min, and then magnetically stirred for 10 min at a speed of 500 r / min.

[0050] (4) Using an electrochemical workstation and a three-electrode system, the copper-filled silicon wafer electroplated in step (2) is used as a working electrode, the platinum electrode is used as a counter electrode, and Ag / AgCl saturated potassium chloride is used as a reference electrode. The distance between the working electrode and the counter electrode is 3 cm. The working electrode, the counter electrode and the reference electrode are placed in an electrolytic cell filled with sodium hydroxide solution for constant potential oxidation. The oxidation potential is -150 mV relative to the reference electrode and the temperature is 25°C.

[0051] (5) After 2 h of oxidation, the electrochemical workstation was turned off, the working electrode was taken out of the solution, rinsed with deionized water, and then dried to obtain Cu(OH)2 nanowire array micro-bumps.

[0052] (6) The Cu(OH)2 nanowires were placed in an annealing furnace, the temperature was raised to 200°C at a rate of 10°C / min and kept at that temperature for 2 h, and then air-cooled to obtain a CuO nanowire array.

[0053] (7) To prepare an electrochemical reduction solution of CuO, 5.6 g of potassium hydroxide was added to 100 mL of deionized water, and the mixture was ultrasonically dispersed for 10 min, and then magnetically stirred for 10 min at a speed of 500 r / min.

[0054] (8) Using an electrochemical workstation and a three-electrode system, the sample in step (6) is used as a working electrode, a platinum electrode is used as a counter electrode, and Ag / AgCl saturated potassium chloride is used as a reference electrode. The distance between the working electrode and the counter electrode is 3 cm. The working electrode, the counter electrode, and the reference electrode are placed in an electrolytic cell filled with potassium hydroxide solution and subjected to constant potential polarization. The polarization potential is -1.0 V relative to the reference electrode and the temperature is 25°C until the current no longer changes and the surface of the working electrode changes from black to reddish brown.

[0055] (9) The copper nanowire array substrate of the working electrode was taken out, and the residual solution on the surface was cleaned with ethylene glycol, and then placed in an ethylene glycol solution containing 0.5 g PVP, 0.1 g ascorbic acid, and 0.5 g glycerol. The substrate was placed in a low vacuum environment of 0.08 MPa for 20 min to allow the organic reducing substances to evenly cover the copper nanowires.

[0056] (10) Align the bumps of the copper nanowire array substrate coated with an organic reducing film on the surface, put it into a hot press bonding machine, apply a pressure of 5Mpa in an air environment, first heat it to 200℃ at a heating rate of 50℃ / min, keep it warm for 10min, then heat it to 250℃ at 10℃ / min, keep it warm for 60min, then take out the bonded sample and air cool it to room temperature. The shear strength of the bonded joint is tested, and the strength is higher than 10Mpa.

[0057] Example 3

[0058] (1) A metal seed layer of 20 nm Ti and 200 nm Cu was magnetron sputtered on a silicon substrate, and then a photoresist was spin-coated on the substrate, baked, exposed and developed.

[0059] (2) Electroplating and filling copper pillars: The substrate in step (1) is used as a cathode for electroplating and filling copper. After filling, it is washed with deionized water and dried with cold air for standby use.

[0060] (3) Preparation of anodized copper nanowire solution: 1.0 g of sodium hydroxide was added to 100 mL of deionized water, the solution was ultrasonically dispersed for 10 min, and then magnetically stirred for 10 min at a speed of 500 r / min.

[0061] (4) Using an electrochemical workstation and a three-electrode system, the copper-filled silicon wafer electroplated in step (2) is used as a working electrode, the platinum electrode is used as a counter electrode, and Ag / AgCl saturated potassium chloride is used as a reference electrode. The distance between the working electrode and the counter electrode is 3 cm. The working electrode, the counter electrode and the reference electrode are placed in an electrolytic cell filled with sodium hydroxide solution for constant potential oxidation. The oxidation potential is -100 mV relative to the reference electrode and the temperature is 25°C.

[0062] (5) After 2 h of oxidation, the electrochemical workstation was turned off, the working electrode was taken out of the solution, rinsed with deionized water, and then dried to obtain Cu(OH)2 nanowire array micro-bumps.

[0063] (6) The Cu(OH)2 nanowires were placed in an annealing furnace, the temperature was raised to 200°C at a rate of 10°C / min and kept at that temperature for 2 h, and then air-cooled to obtain a CuO nanowire array.

[0064] (7) To prepare an electrochemical reduction solution of CuO, 0.56 g of potassium hydroxide was added to 100 mL of deionized water, and the mixture was ultrasonically dispersed for 10 min, and then magnetically stirred for 10 min at a speed of 500 r / min.

[0065] (8) Using an electrochemical workstation and a three-electrode system, the sample in step (6) is used as a working electrode, a platinum electrode is used as a counter electrode, and Ag / AgCl saturated potassium chloride is used as a reference electrode. The distance between the working electrode and the counter electrode is 3 cm. The working electrode, the counter electrode, and the reference electrode are placed in an electrolytic cell filled with potassium hydroxide solution and subjected to constant potential polarization. The polarization potential is -1.2 V relative to the reference electrode and the temperature is 25°C until the current no longer changes and the surface of the working electrode changes from black to reddish brown.

[0066] (9) The copper nanowire array substrate of the working electrode was taken out, and the residual solution on the surface was cleaned with ethylene glycol, and then placed in glycerol containing 0.1 g of ascorbic acid, and allowed to stand in a low vacuum environment of 0.08 MPa for 20 min to allow the organic reducing substances to evenly cover the copper nanowires.

[0067] (10) Align the bumps of the copper nanowire array substrate coated with an organic reducing film on the surface, put it into a hot press bonding machine, apply a pressure of 5Mpa in an air environment, first heat it to 200℃ at a heating rate of 10℃ / min, keep it warm for 10min, then heat it to 250℃ at 10℃ / min, keep it warm for 20min, then take out the bonded sample and air cool it to room temperature. The shear strength of the bonded joint is tested, and the strength is higher than 10Mpa.

[0068] Example 4

[0069] The method described in Example 3 is the same as that in Example 3, except that the ingredients in step (9) are a mixture of 0.5 g citric acid and 5 g glycerol. Finally, the bonded joint is subjected to a shear strength test, and the strength is higher than 10 MPa.

[0070] Example 5

[0071] The method described in Example 3 is the same as that in Example 3, except that the ingredients in step (9) are a mixture of 0.5 g 3-dimethylamino-1,2-propylene glycol (DMAPD) ​​and 5 g glycerol. Finally, the bonded joint is subjected to a shear strength test, and the strength is higher than 10 MPa.

[0072] Example 6

[0073] The method described in Example 3 is the same as that in Example 3, except that the ingredients in step (9) are a mixture of 0.5 g formic acid and 5 g glycerol. Finally, the bonded joint is subjected to a shear strength test, and the strength is higher than 10 MPa.

[0074] Example 7

[0075] The method described in Example 3 is the same as that in Example 3, except that the ingredients in step (9) are a mixture of 0.5 g acetic acid and 5 g glycerol. Finally, the bonded joint is subjected to a shear strength test, and the strength is higher than 10 MPa.

[0076] Comparative Example 1

[0077] The copper nanowire interconnect was prepared according to the method described in Example 3, which differs from Example 1 in that the working voltage applied during the electrochemical reduction process was -0.6 V relative to the reference electrode.

[0078] Since CuO needs to be at a certain potential to undergo electrochemical reduction to Cu, when the applied working voltage is small, CuO nanowires cannot be transformed into Cu nanowires, resulting in a decrease in the bonding strength of the copper nanowire interconnects.

[0079] Comparative Example 2

[0080] The copper nanowire interconnect was prepared according to the method described in Example 1, except that the organic reducing substance consisted of polyethylene glycol and ethylene glycol.

[0081] The organic reducing agent has the functions of anti-oxidation and reducing copper oxides. When the content of reducing organic matter is low, the oxidized copper nanowires cannot be reduced to copper, resulting in a decrease in the bonding strength of the copper nanowire interconnects.

Claims

1. A method for bonding surface nanostructured copper pillars in an air environment, characterized in that: The steps include: (1) first depositing a metal Ti seed layer on a silicon substrate, and then depositing a metal Cu seed layer; then applying a photoresist on the silicon substrate by spin coating, and then baking, exposing and developing in sequence; (2) preparing a Cu(OH)2 nanowire solution: adding sodium hydroxide into deionized water and stirring until the sodium hydroxide is completely dissolved; (3) Electrodepositing copper pillar array: electroplating copper to fill the silicon substrate after photolithography in step (1), washing with deionized water and drying with nitrogen after electroplating; (4) Preparation of Cu(OH)2 nanowires: The silicon substrate obtained in step (3) is used as an anode, a platinum sheet is used as a cathode, and an Ag / AgCl saturated potassium chloride electrode is used as a reference electrode. The cathode, anode and reference electrode are placed in an electrolytic cell of the nanowire solution obtained in step (2), and an electrochemical workstation three-electrode system is used for oxidation. Anodization is performed at a certain voltage range using a constant potential method. After the anodization is completed, the power supply is turned off, the silicon substrate of the anode is taken out from the nanowire solution, rinsed with deionized water and dried, and Cu(OH)2 nanowires are formed on the top of the copper column; (5) annealing the Cu(OH)2 nanowires obtained in step (4) in air to thermally decompose the Cu(OH)2 nanowires into CuO nanowires; (6) preparing potassium hydroxide electro-reducing solution: adding potassium hydroxide into deionized water and stirring until completely dissolved; (7) electro-reducing the CuO nanowires to Cu nanowires: using the silicon substrate with CuO nanowires grown thereon obtained in step (5) as a cathode, graphite as an anode, and an Ag / AgCl saturated potassium chloride electrode as a reference electrode, and performing constant potential polarization in the potassium hydroxide electro-reduction solution obtained in step (6) using an electrochemical workstation until the current is stable and the cathode surface changes from black to reddish brown, the CuO nanowires are electro-reduced to Cu nanowires, and copper pillar array bumps with Cu nanowires on the surface are obtained on the silicon substrate; (8) The silicon substrate with Cu nanowire array bumps obtained after electro-reduction is placed in an organic reducing agent, and in a low vacuum environment below 0.1 MPa, the organic matter forms a dense protective film on the Cu nanowires. Then, the silicon substrate with the Cu nanowire array bumps is taken out, the upper and lower bumps of the two silicon substrates are aligned, and the two silicon substrates are placed in a bonding machine, and hot-pressed sintering is performed at 150-300° C. and 0-20 MPa for 10-30 min.

2. The method for bonding surface nanostructured copper pillars in an air environment according to claim 1, characterized in that: In step (1), the thickness of the metal Ti seed layer is 10-100 nmTi, and the thickness of the metal Cu seed layer is 100-500 nm.

3. The method for bonding surface nanostructured copper pillars in an air environment according to claim 1, characterized in that: In step (2), the concentration of sodium hydroxide is 0.1-1 M / L.

4. The method for bonding surface nanostructured copper pillars in an air environment according to claim 1, characterized in that: The working voltage applied in step (4) is -200mV to -100mV relative to the reference electrode.

5. The method for bonding surface nanostructured copper pillars in an air environment according to claim 1, characterized in that: In step (5), the annealing temperature of the Cu(OH)2 nanowires is 180-220°C, and the annealing time is 1-3h.

6. The method for bonding surface nanostructured copper pillars in an air environment according to claim 1, characterized in that: In step (7), the concentration of potassium hydroxide is 0.1-1 M / L.

7. The method for bonding surface nanostructured copper pillars in an air environment according to claim 1, characterized in that: The working voltage applied in step (7) is -0.8V to -1.2V relative to the reference electrode.

8. The method for bonding surface nanostructured copper pillars in an air environment according to claim 1, characterized in that: The organic reducing agent used in step (8) is: one or a mixture of two or more of ethylene glycol, polyethylene glycol, polyvinyl pyrrolidone, ascorbic acid, citric acid, glycerol, 3-dimethylamino-1,2-propylene glycol, formic acid, and acetic acid.

9. The method for bonding surface nanostructured copper pillars in an air environment according to claim 1, characterized in that: The diameters of the Cu(OH)2 nanowires and CuO nanowires are 50-200nm.

Citation Information

Patent Citations

  • Copper nanometer wire-based copper-copper bonding process

    CN104637831A

  • Copper nanorod based copper-tin-copper bonding process and structure

    CN105679683A

  • High-density copper pillar bump bonding interconnection method

    CN114582744A

  • Wafer-level copper-copper bump interconnection structure and bonding method thereof

    CN116153860A

  • Silver-coated copper nanowire and preparation method therefor

    US20170140846A1